Edukasi Pijat Bayi melalui Program SENTUH untuk Peningkatan Pengetahuan dan Keterampilan Ibu di Posyandu Mekar Jaya - Nurrahmi Umami; Rahmatuz Zulfia; Nazwa Manurung; Annisa Eka Permatasari; Tanti Tri Lestary (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2025)
Child health and early childhood development are strongly influenced by the quality of maternal care, including simple stimulation such as infant massage. However, parenting literacy and practical skills in infant massage remain low among many mothers in Tarakan, North Kalimantan. This lack of knowledge leads to suboptimal stimulation during early childhood, which is a critical period for growth and development. Therefore, the SENTUH Program (Sehat, Nyaman, Tumbuh Harmonis/Healthy, Comfortable, Harmonious Growth) was implemented as a community service initiative to improve mothers’ capacity in infant massage as a form of stimulation and to strengthen mother–child bonding. The aim of this program was to enhance mothers’ knowledge and skills in infant massage through interactive education, demonstrations, and role play. The methods included socialization, training, and hands-on practice. Interactive lectures were delivered on the benefits of infant massage, developmental milestones, and responsive parenting. Infant massage demonstrations were conducted by facilitators using dolls, followed by direct practice by participants. Role play was applied to train empathic communication between cadres, mothers, and infants, while also improving cadres’ facilitation skills in posyandu activities. Evaluation was carried out through pretest–posttest assessments and direct observation of infant massage practice. The results indicated a significant improvement in both knowledge and skills among mothers and cadres. Most participants were able to describe the benefits of infant massage, identify correct steps, and perform the practice independently. Cadres also showed improved ability to facilitate mother classes after training. SENTUH Program proved effective in enhancing mothers’ and cadres’ knowledge and skills in infant massage. This initiative strengthens the role of families and community health posts in supporting optimal child growth and development.